Perceived Impacts of Climate Change on Economic Activities and Adaptation Strategies: A Case Study from Cold Desert of Ladakh, India - Tsering Tashi; Falendra Kumar Sudan (Regional Economic Development Research, 2021)
This paper aims at identifying the perception of local indigenous Peoples’ living in the cold desert area of Nubra valley (Ladakh), India, on climate variability resulting in extreme events such as floods and cloudbursts and their impacts on various economic activities such as agricultural productivity, land degradation, soil erosion, water availability, and forest resources. It also aims to ascertain the vulnerability of the key sectors such as forest, agriculture and water sources, and local adaptation strategies to adapt to climate variability and extreme events. Stratified random sampling technique was adopted to select the sample size. The study is based on the primary data and information collected from 288 sample households in three blocks i.e., Diskit, Panamik, and Turtuk through semi-structured interviews, questionnaires, focus group discussions, and PRI tools. Study findings revealed that more than 90 percent of overall households’ respondents of three blocks observed that temperature has been increased and low rainfall/snowfall over the last three decades. The result showed that the majority of respondents admitted that land degradation, severe soil erosion and shortage of water, low agricultural productivity, and decline in forest resources are major climate related problems due to low rainfall/snowfall, increase temperature, and natural disasters. To alleviate these problems, local people have implemented various adaptation strategies such as mixed farming, more plantations of trees, organic farming, and changing crop patterns. The policy recommendations for appropriate adaptation strategies are in consideration with the knowledge of local indigenous peoples and their perception of climate change. The study could be helpful to policymakers to design appropriate adaptation strategies to cope up with the impacts of climate change.